Intraoperative Hyperglycemia Augments Ischemia Reperfusion Injury in Renal Transplantation: A Prospective Study - Justin Parekh; Claus U. Niemann; Kim Dang; Ryutaro Hirose (Journal of Transplantation)
Background. Diabetes is a risk factor for delayed graft function in kidney transplantation, and hyperglycemia increases ischemia reperfusion injury in animal models. Methods. To explore the role of perioperative hyperglycemia in ischemia reperfusion injury, we conducted a prospective study of 40 patients undergoing living donor renal transplantation. Blood glucose levels were monitored intraoperatively, and serum samples were obtained at the time anesthesia was induced and one hour after allograft reperfusion. The percentage change in neutrophil gelatinase-associated lipocalin (NGAL), a protein whose expression is increased with renal ischemia, was then used to determine the extent of injury. Results. In a multivariate model including recipient, donor, and transplant factors, recipient blood glucose >160 mg/dL at the time of allograft reperfusion (β 0.19, P-value < 0.01), warm ischemia time >30 minutes (β 0.11, P-value 0.13), and recipient age (β 0.05, P-value 0.05) were associated with percentage change in NGAL. These same predictors were associated with the percentage change in creatinine on postoperative day 2. Conclusions. Hyperglycemia is associated with increased ischemic injury in renal transplantation. Both creatinine and NGAL, a marker of ischemic injury and renal function, fall less rapidly in patients with elevated blood glucose.